'& thus ended the buisinisse': A buggery trial on the East India Company ship Mary in 1636. Issue 4 (2nd October 2017) - Massarella, Derek
Abstract : Not much archival information survives about buggery trials at sea in the seventeenth century. A trial aboard the East India Company's ship, the Mary, at Surat in 1636 is an exception and is well documented. This article provides a detailed account of the trial, placing it within the broader contexts of naval discipline, the judicial powers devolved to the East India Company by the monarch and, more generally, the question of same-sex relations both at sea and on land in seventeenth-century England.